Legality of Attraction to Administrative Responsibility: Concept, Content and Main Requirements - Sergei V. Yarkovoi (Сибирское юридическое обозрение)
The article analyzes the concept, content and requirements of the legality of the activities of executive authorities, other public authorities to bring individuals and legal entities to administrative responsibility. The Author's definition of the concept of the legality of such activities is given, the system of requirements for its legality is stated, a proposal is made to clarify the provisions of Art. 1.6 of the Code of the Russian Federation on Administrative Offenses.